Growth and yield of groundnut (Arachis hypogaea) under varying levels of gypsum and zinc application in Iran - ZIBA SHOKRI; MAJID ASHOURI; HAMIDREZA DOROUDIAN; NASER MOHAMMADIAN ROSHAN; SEYED MOSTAFA SADEGHI (The Indian Journal of Agricultural Sciences, 2024)
A field study was carried out during spring season of 2021 and 2022 at Astaneh-ye Ashrafiyeh, Guilan, (Islamic Azad University, Lahijan, Iran) northern Iran to study the effect of natural gypsum (NG) and zinc (Zn) foliar application on peanut (Arachis hypogaea L.) yield and quality. NG was applied at 4 levels [0 (NG0); 10 (NG10); 20 (NG20); and 30 (NG30) g/m2] and Zn nano-chelates were applied at 3 levels [0 (Zn0); 1 (Zn1); and 2 (Zn2) g/L)] as foliar application. The results showed that the interaction of NG × Zn was significant for leaf chlorophyll, kernel and pod number per plant, kernel protein, oil content and and kernel yield during both the years. The interaction of NG × Zn was also significant on the P, S and Fe of kernels. Leaf K and Fe contents were significantly influenced only by NG. The comparison between mean revealed that the highest kernel yield (5839 kg/ha), kernel number (93.5 kernels/plant), pod number (66.3 pods/plant) and kernel S (0.384%) were recorded from the plots applied with NG20 + Zn2. The highest leaf chlorophyll (3.83 mg/kg FW) and oil content (46.09%) were related to the treatment NG20 + Zn1. The plots applied with NG10 + Zn2 exhibited the highest kernel protein (17.92%). Based on the results, it can be stated that the NG and Zn as soil application and foliar spray respectively, improved peanut yield and qualitative traits hence can be recommended for similar climatic conditions.